A multilevel investigation of the leadership factors on food safety promotive and prohibitive voices through food safety consciousness. (June 2021) - Yu, Heyao; Guchait, Priyanko; Achyldurdyyeva, Jennet; Paşamehmetoğlu, Ayşın
Abstract: Little research has empirically examined how leadership factors influence food safety promotive and prohibitive voice differently. Also, little research has examined the moderating effects of leadership on the relationship between individual antecedents and promotive and prohibitive voice as contextual factors. The current study developed and tested a multilevel model regarding how leaders' food safety orientation and authentic leadership influence employees' food safety-related prohibitive and promotive voices. The results showed that leaders' food safety orientation is an important antecedent of employees' food safety prohibitive and promotive voices and both relationships are partially mediated by employees' food safety consciousness. Additionally, the results suggested that authentic leadership works as a contextual factor that moderates the relationship between employees' food safety consciousness and food safety prohibitive voice, but the moderating effect is not significant in the relationship between employees' food safety consciousness and promotive voice. The results of this study provide meaningful insights for researchers by empirically examining how leadership factors influence food safety prohibitive and promotive voice differently as antecedent and moderator. Highlights: Leader safety orientation is an antecedent of food safety promotive and prohibitive voices. Food safety consciousness mediates leader safety orientation and employees' voice. Authentic leadership moderates the path of food safety consciousness on food safety prohibitive voice. Authentic leadership does not moderate the relationship between food safety consciousness on promotive voice.